2019
DOI: 10.1002/smtd.201900495
|View full text |Cite
|
Sign up to set email alerts
|

Delaminating Vanadium Carbides for Zinc‐Ion Storage: Hydrate Precipitation and H+/Zn2+ Co‐Action Mechanism

Abstract: Aqueous zinc (Zn) ion energy devices have demonstrated remarkable significance as a substitute of their lithium counterparts. Developing cheap and nontoxic electrode active materials is crucial for maximizing the storage of Zn ions. As a new star of 2D materials, MXenes can pose unique layered structure and abundant surface chemistry, largely benefiting the surface storage of ions. Herein, carbon nanotube (CNT) delaminated V2C MXene (DV2C@CNT) has been demonstrated, as a promising electrode for high‐performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(61 citation statements)
references
References 46 publications
0
61
0
Order By: Relevance
“…After that, Yuan et al [117] also found that the δ-Na 0.44 MnO 2 •1.5H 2 O/Zn battery performed the similar Zn 2+ /H + dual ions reaction mechanism. Besides, excepting the Mn-based oxide cathode materials, such storage mechanism was also observed in several vanadium-based cathode systems, such as the NaV 3 O 8 •1.5H 2 O/ Zn battery reported by Wan et al, [118] as well as the carbon nanotube (CNT) delaminated V 2 C MXene (DV 2 C@CNT)/Zn battery reported by Wang et al [28] Unlike the Zn 2+ /H + dual ions storage process, Kundu et al [104] reported a unique Zn 2+ /H 2 O co-insertion storage mechanism in a Zn 0.25 V 2 O 5 •nH 2 O/Zn battery system ( Figure 3c). They employed the operando X-ray diffraction to investigate the electrochemical behavior.…”
Section: Ions/molecules Co-insertion/extraction Mechanismmentioning
confidence: 80%
See 1 more Smart Citation
“…After that, Yuan et al [117] also found that the δ-Na 0.44 MnO 2 •1.5H 2 O/Zn battery performed the similar Zn 2+ /H + dual ions reaction mechanism. Besides, excepting the Mn-based oxide cathode materials, such storage mechanism was also observed in several vanadium-based cathode systems, such as the NaV 3 O 8 •1.5H 2 O/ Zn battery reported by Wan et al, [118] as well as the carbon nanotube (CNT) delaminated V 2 C MXene (DV 2 C@CNT)/Zn battery reported by Wang et al [28] Unlike the Zn 2+ /H + dual ions storage process, Kundu et al [104] reported a unique Zn 2+ /H 2 O co-insertion storage mechanism in a Zn 0.25 V 2 O 5 •nH 2 O/Zn battery system ( Figure 3c). They employed the operando X-ray diffraction to investigate the electrochemical behavior.…”
Section: Ions/molecules Co-insertion/extraction Mechanismmentioning
confidence: 80%
“…Unlike the pure Zn 2+ storage, such mechanism is proceeding along with Zn 2+ and other ions (H + )/molecules (H 2 O) in a sequential order, owing to their difference at thermodynamics and reaction energy barrier. [97] For the first time, Wang et al [28] proposed a consequent H + and Zn 2+ dual ions insertion/extraction mechanism in the α-MnO 2 /Zn battery ( Figure 3b). In their experiments, the cyclic voltammetric (CV) curve exhibited two well separated reversible redox peaks, galvanostatic intermittent titration technique (GITT) measurement also indicated the distinct reaction kinetics of that two peaks, which possibly imply the existence of another type of ions insertion excepting the Zn 2+ .…”
Section: Ions/molecules Co-insertion/extraction Mechanismmentioning
confidence: 99%
“…Therefore, it can indicate the local structure of active atoms including the bond length and coordination number. [ 77 ] Naturally, the structure and mechanism of optimized MXenes were studied by using XAFS in the application of catalysis, [ 78 ] supercapacitors, and batteries [ 79 ] with ideal results, showing its indispensability in the development of MXenes.…”
Section: Synchrotron Radiation Characterizationsmentioning
confidence: 99%
“…In 2019, our group investigated the structure of delaminated V 2 C MXene and CNT composite during the supercapacitor application in H 2 SO 4 electrolyte. [ 79 ] First, we prepared the free‐standing film of delaminated V 2 C MXene and CNT composite (DV 2 C@CNT) by following the procedure as shown in Figure 7c‐i. The obtained DV 2 C@CNT film was compact with uniformly dispersed CNT in between DV 2 C layers with a cross‐stacking structure (Figure 7c‐ii).…”
Section: Synchrotron Radiation Characterizationsmentioning
confidence: 99%
“…7c). Wang et al [76] designed an electrode of Zn-ion supercapacitor, where the carbon nanotube (CNT) network uniformly mixed with V 2 CT x MXenes (Fig. 7d-f).…”
Section: Applicationmentioning
confidence: 99%